Development in Rural areas: Environmental analysis and environmental management for sustainable regional development - Monheim, Heiner (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This article discusses the concept underlying Special Research Area 522 — “Environment and Region”, set up in July 1999 at the University of Trier. Since the work of this special research area is still in its initial stages, the author, the co-ordinator of this research area, is not yet in a position to present concrete findings. The focus of the article lies rather in outlining the substantive framework for the first and subsequent phases of funding.
Keywords: Article